Evaluation of Efficacy and Cost-effectiveness of Outpatient Resection of Endometrial Pathologies in a University Hospital in the UK - Kshitij Jamdade; PapaYaw Opokuansah; Sanjaya Kalkur (Wolters Kluwer Medknow Publications, 2024)
Objective The objective of the study was to evaluate the efficacy of outpatient MyoSure procedures and their cost-effectiveness. Design A retrospective analysis of patients who had outpatient MyoSure procedures from November 2019 to November 2020. Subjects and Methods Data were collected retrospectively from electronic patient records (hysteroscopy reports, clinic notes, clinic letters, and histopathology results) from November 2019 to November 2020 and analyzed using Microsoft Excel and SPSS software. Results Fifty-eight outpatient MyoSure procedures were performed from November 2019 to November 2020. The mean age was 53.13 years (22-81 years) and the mean body mass index was 29.65 kg/m2 (18-51 kg/m2). We found that our service has a success rate of 93.1% (54/58), a completion rate of 92.59% (50/58), and a discharge rate of 82.75% (48/58). The complete resection rate for polyps was 100% and for fibroids, it was 76.47%. When compared to the same procedure performed under general or regional anesthesia in a day surgery setting, an outpatient MyoSure procedure saves around 1117 GBP per procedure, for the Trust. We have compared data for the first 6 months to the following 6-month period. There were significant improvements in the success rate, completion rate, and discharge rate, also accompanied by a reduced complication rate. This is likely due to improved operators' experience in performing the procedure, and also the increased use of local anesthetic injection and cervical dilatation. Conclusions Outpatient MyoSure procedures are feasible, efficacious, safe, acceptable, and cost-effective. The use of local anesthetic and cervical dilation has been associated with improved success rates.